MANAJEMEN GUGUS PENDIDIKAN ANAK USIA DINI (Studi Kasus pada Juara Nasional Gugus PAUD Kota Malang) - Muhamad Suhardi (Jurnal Paedagogy, 2014)
This study aims to describe all activities and phenomena in the study of educational management in PAUD clusters which include planning, organizing, implementing and evaluating groups. The approach used is a qualitative approach with a case study model. Data collection was carried out through interviews, documentation data, and observation data regarding the implementation of PAUD groups. Researcher is the main instrument supported by interview, observation, and documentation guidelines. Analysis of research data using an interactive model which includes data collection, data reduction, data display, and data verification / conclusion. The results showed that; (1) Cluster planning begins with a plan to form a cluster up to a description of the cluster budget; (2) Cluster organization includes; Determination of cluster administrators, KKG, KKKP, PAUD cluster committees up to the creation of organizational work mechanisms; (3) The implementation of the group work program includes; implementation of work programs based on initial work planning through to collaborating with parents, government and local agencies to make a positive contribution to cluster development; (4) cluster evaluation includes; evaluation is carried out after the work program is implemented, monthly reports, and annual reports of the PAUD cluster.